EFECTO DE PROBIÓTICOS EN EL ALIMENTO DE MARRANAS SOBRE LOS PARÁMETROS PRODUCTIVOS DE LECHONES - Lázaro D., César (2005)
Fifty sows of the PIC genetic line and their piglets were used to determine the effect of food additive probiotic (Saccharomyces cerevisiae 12 x 109 CFU/g, Bacillus subtilis15 x 1010 CFU/g and Bacillus coagulans 15 x 1010 CFU/g) added to conventional diets. The sows were randomly divided in two groups: Probiotic and Control. The Control group was fed with the gestation diet (MG) for 3 weeks prior to farrowing and the Probiotic group was fed with the MG diet supplemented with the probiotic. During this period the sows received a restricted amount of concentrate (2-3 kg/day/animal). The Control group during the lactation period was fed ad libitum with the lactation diet (ML) and the Probiotic group was fed with the ML diet supplemented with the probiotic. Body weight and feed intake was registered in sows while in piglets was recorded litter size, body weight at birth and at weaning, and mortality and morbidity. The results showed that the probiotic supplemented to the sow diet significantly affected birth body weight (p<0.05). Moreover, there were minor differences in piglet mortality and morbidity due to gastro enteric disorders.